Physical Properties and Diffusion-Coefficient Calculation of Iron Diffused Bi-2223 System - Öztürk, Özgür; Aşıkuzun, Elif; Kaya, Sedanur; Coşkunyürek, M.; Yıldırım, Gürcan; Yılmazlar, M.; Terzioğlu, Cabir (Springer Science and Business Media LLC, 2012)
This study includes two parts: (I) investigation of the effect of different annealing time (10 h, 30 h, and 60 h) on physical, superconducting, and microstructural properties of Fe-diffused Bi-2223 superconductor ceramics prepared by the conventional solid-state reaction method with the aid of the X-ray diffraction (XRD), scanning electron microscopy (SEM), dc resistivity (ρ–T) and transport critical current density (J c ) measurements, and (II) determination of the diffusion coefficient and the activation energy of iron in the Bi-2223 system. In the former part, the zero-resistivity transition temperature (T c ), phase purity, volume fraction, hole-carrier concentration, lattice parameters, surface morphology, texturing, crystallinity, grain connectivity, grain size, and room temperature resistivity values of the bulk samples are found and compared with each other. The results obtained show that both the zero resistivity transition temperature (T c ) and transport critical current density (J c ) regularly enhance with the increment in the diffusion-annealing time. The maximum T c of 107±0.2 K and J c of 50.0 A cm−2 are observed for the sample annealed at 830 °C for 60 h. As for the XRD investigations, according to the refinement of cell parameters done by considering the structural modulation, the enhancement in the diffusion-annealing is confirmed by both a decrease of the cell parameter a and an increase of the lattice parameter c of the samples, meaning that the greatest Bi-2223 phase fraction belongs to the sample annealed at 830 °C for 60 h. Moreover, SEM images display that the sample has the best crystallinity, grain connectivity, and largest grain size. Based on the results, the superconducting and microstructural properties improve with the increase in the diffusion-annealing time. In the latter part, Fe diffusion in the Bi-2223 system is examined in a range of 500–830 °C by the variation of the lattice parameters evaluated from the XRD patterns. The temperature dependence of the Fe diffusion coefficient is described by the Arrhenius relation D=4.27×10−5exp(−1.27±0.10) eV/kBT, and the related activation energy of the iron in the Bi-2223 system is found to be about 1.27 eV. The relatively low value of activation energy obtained illustrates that the migration of the Fe ions primarily proceeds through defects such as pore surfaces and grain boundaries in the polycrystalline structure, leading to the improvement of the microstructural and superconducting properties of the samples, supported by the results of part I. All in all, the aim of the present study is not only to analyze the role of diffusion-annealing time on superconducting and microstructural properties of Fe-diffused Bi-2223 superconductors, but also to find the diffusion coefficient and activation energy of Fe in the Bi-2223 system.
Keywords: Fe-diffused Bi-2223; Diffusion Coefficient; XRD; Physics; SEM